Deixis in Kurdish-Khoshnawaty Sub-dialect and English-British Dialect: "Acomparative study" - Rasol, Khesro; Ahmed, Rawand (Humanities Journal of University of Zakho, 2021)
The title of the paper is "Deixis in Kurdish-Khoshnawaty Sub-dialect and English-British Dialect." The purpose is to study the deictic expressions between the two languages in order to show points of similarities and differences. The term deixis is a linguistic phenomenon which includes time, place, social, and text; these are expressed through deixis as they have roles in speech. The deixis are shown through personal pronouns, demonstratives, adverbs of time and place, tenses, and kinship terms. Deixis relate language and context so that they clarify the ambiguities and provide better understanding. The paper comprises of an introduction and two sections. The introduction mentions title, reason of choosing the topic, method, scope, and content of the paper. The reason behind choosing the title is that there has not been yet any comparative study of such kind between Kurdish and English, besides; the study paves the way for Kurdish learners of English to better understand English. The method of the research is synchronic, descriptive and comparative, and the level is pragmatic though it also uses semantic and syntactic level when necessary. The samples of Khoshnawaty sub-dialect were gathered from daily language speakers whereas those of British English were extracted from written resources. The first section describes deixis in Kurdish (Khoshnawaty Sub-dialect). The second section is devoted to deixis in English (British Dialect). This section mentions the use of linguistic elements. There is also a conclusion which demonstrates points of similarities and differences between the two languages. The paper ends with a list of references.